Peran teknologi jaringan komputer dalam penyebaran informasi di Perpustakaan SMKN 1 Trenggalek - Linda Lailatul Nur Hanifah; Nurwulan Saraswati (IJAL (Indonesian Journal of Academic Librarianship), 2020)
The purpose of this study was to determine the role of computer network technology in the dissemination of information at the Trenggalek Vocational High School 1 Library. This study covers the efforts of librarians in disseminating information and also examines the role of computer network technology in theVacational High School 1 Trenggalek Library. The method used in this research is descriptive qualitative method. Data collection techniques in this study use direct observation (observation) and also interviews. The researcher also had time to ask some questions that were related to the research conducted. Participants in this study were librarians and also IT staff at the Vacational High School 1 Trenggalek Library. Information dissemination is done by distributing flyers and pamphlets in print and digital forms to school residents, especially those intended by students and teachers. Direct submission in the form of an announcement in the form of an appeal and in the form of a user education is intended to educate students about the procedures for utilizing collections and also the introduction of libraries. The information submitted is usually in the latest collections in the library, both books and systems that have been developed. Through a computer network, the processes related to library services can be done quickly and automatically, starting from searching library materials, borrowing, returning, and also calculating fines.